Knowledge Triumphant: The Concept of Knowledge in Medieval Islam by Franz Rosenthal (Leiden: Brill, 2007. 355 pages.) (American Journal of Islam and Society, 2008)
Brill’s new “Classics in Islam” series, a systematic reprinting of some ofthe seminal works in Islamic studies that have been out of print fordecades, is a welcome initiative.As Dimitri Gutas, a former student, indicatesin his introduction, Rosenthal’s achievement in this monograph is outstandingwithin an exceptionally productive and influential career. It isalso somewhat unusual that a work first published over thirty years ago stillremains unsurpassed, even if one may question some of the argument’sdetails and tendencies. Rosenthal often worked with manuscripts andunedited sources and, while we have the luxury of criticizing his judgmentsbased on our access to superior critical editions, the contribution of the bookremains singular.As befits a social and intellectual historian, Rosenthal’s survey commenceswith the philology of the word knowledge (`ilm) and works throughinstances in early Islam andArabic poetry before moving on to chapters ondefinition, theology, Sufism, philosophy, and finally concluding with a chapteron the social contexts and uses of knowledge. While there are now anumber of works that deal with aspects of these chapters, no one hasattempted to reconstruct a survey quite like this. Each chapter could well bethe subject of monographs and, as Gutas suggests, numerous sections couldact as inspiration for “untold dissertations.” Rosenthal begins with the claimthat civilizations tend to revolve around meaningful concepts of an abstractnature that,more than anything else, give themtheir distinctive nature; in thecase of Islam, this is the centrality of knowledge and the pursuit of knowledge.While he shifts from the plural to the singular and back, one retains thecentral point that the field of knowledge is unified. The fact is that Muslimscholars in very different fields of inquiry were able to retain a concept of`ilm that was broadly cognate and transferable ...